The Effectiveness of Imagery Therapy Guide on Pain and Anxiety in URS Perioperative Patients in Lontara Room 2 Lower Front of Urological Surgery, RSUP Dr. Wahidin Sudirohusodo Makassar - Sriwahyuni Sriwahyuni; Sulasri Sulasri; Kadek Ayu Erika; Syahrul Ningrat; Muhajirin Maliga; Nia Kurnia Djalil (Pusat Riset dan Inovasi Nasional, 2023)
Objective: The purpose of this study is to apply Evidence-Based Nursing Practice (EBNP) activities based on the concepts and models of nursing theory. Method: EBP implementation design used is true experimental with research design Guide imagery. The sampling technique in the implementation of EBP is accidental sampling with nonprobability sampling approach. The population in this study were patients who were at Wright Patterson Medical Center in Ohio with planned surgery on the head and neck area of 44 people divided into 2 groups. Results: giving guide imagery before surgery can reduce the pain as measured by using VAS. The results showed that the pain level was measured after 1 hour postoperatively and 2 hours postoperatively. At the initial measurement, there was no significant difference between the control group and the intervention group with a p value of 0.057. After 2 hours postoperatively, there was a significant difference in pain level between the control group and the intervention group with a p value of 0.041. Conclusion: The implementation of evidence based practice using guide imagery as a therapy before the patient is operated is proven to reduce the level of pain and anxiety of the patient.